التجربة الذاتية عند الشاعر العثماني محمد بن مخزوم الإصبعي (دراسة تحليلية) - الدكتور غسّــان بن صالح عبد المجيد; محمد أحمد ناشي (Al Manhal Research Journal, 2024)
The Subjective experience is one of the most important components of a poetic work, as it reflects the thoughts and feelings of the poet and his personal experience, plays an essential role in the formation of the poet's literary identity and in presenting his own vision of the world. Therefore, this study aims to explore how the subjective experience is embodied in Mohammed bin makhzoum's finger poetry, and analyze the impact of his life experiences on his poetic production. The subjective experience of our poet is primarily the expression of his feelings and thoughts, his personal memories through his poems. While we are sure that these experiences vary from one poet to another, as they depend on their social, cultural, and psychological backgrounds, in addition to the events they have experienced in their lives.